Karakteristik Pertumbuhan Mucuna (Mucuna bracteata L.) dengan Metode Sungkup dan Tidak Disungkup di Kabupaten Serdang Bedagai - Handika, Bagus; Saragih, Wismaroh Sanniawati Br.; Jabat, Yelfi Yana Linda Br. (JURNAL AGROPLASMA, 2024)
Covering of Mucuna bracteate L. cuttings plays an important role in the survival rate of Mucuna Bracteata plants, as it helps maintain optimal humidity and temperature levels. The adjustment process after the cover is opened is very important before moving the cuttings to open land. This study aims to measure the impact of covering on the survival rate of cuttings. This study used a Randomized Block Design (RAK). The treatments used were Covered (P1) and Uncovered (P2), by applying Topsoil 3kg (K0), Topsoil 1.5kg + Sand 1.5kg (K1), Topsoil 1.5kg + Black Soil 1.5kg (K2), Topsoil 1.5kg + Cow Manure 1.5kg (K3). This research was conducted from August 10 to September 9, 2024. This research was conducted in the Yard of a House in Ngaraja 1 Village, Dolok Merawan District, Serdang Bedagai Regency. Based on the Least Significant Difference (LSD) Test, Covering and Topsoil (P1K0) consistently showed the best results in terms of number of shoots, tendril length, number of leaves and Root Length. This indicates that covering and topsoil provide optimal conditions for the early growth of Mucuna plants. Topsoil and sand (P1K1) showed the highest root volume. This suggests that the addition of sand to the topsoil may have increased aeration and water drainage, thus encouraging root development. Keywords: covering, vegetative growth, Mucuna bracteata L.